Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Am I doing this right? What's a good way to think about the different f(n)'s. f(n + 1) is the "next" element in the series? f(n) is the current element? The previous element?

Find $f(1), f(3), f(4),$ and $f(5)$ if $f(n)$ is defined recursively by $f(0) = 3$ and for $n = 0,1,2...$

[a.] $f(n+1) = -2f(n)$

\begin{align*} \text{Basis Step: } f(0) = 3& \\ \\ f(0 + 1) = -2(3) = -6 \\ f(1 + 1) = -2(-6) = 12 \\ f(2 + 1) = -2(12) = -24 \\ f(3 + 1) = -2(-24) = 48 \\ f(4 + 1) = -2(48) = -96 \end{align*}$

share|cite|improve this question
up vote 1 down vote accepted

The computations are correct. Yes, $f(n)$ can be thought of as the current element of the sequence, and $f(n+1)$ as the next element. The recurrence (in this case) tells you how to compute the next element, if you know the current one.

share|cite|improve this answer

A clearer way for me to see the recurrence relation is by rewriting it as

$f(0) = 0$

$f(n) = -2f(n-1)$

Looking at it this way says whatever term in the sequence you are interested in is twice the previous term.

share|cite|improve this answer
I agree, this is a much more intuitive way to look at it. Does this mean if I want to change from f(n+1) to f(n) I should subtract 1 from each argument inside f()? – papercuts Feb 10 '13 at 5:40
You can just do a simple change of variable: let $n=m-1$: hence $f(n+1)=f(m)=-2*f(m-1)$ – jesterII Feb 10 '13 at 5:50

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.